A newly discovered teleost disulfide isomerase, thioredoxin domain containing 5 (TXNDC5), from big-belly seahorse (Hippocampus abdominalis): Insights into its molecular and functional properties and immune regulatory functions. (January 2021) - Sandamalika, W.M. Gayashani; Samaraweera, Anushka Vidurangi; Yang, Hyerim; Lee, Jehee
Abstract: The thioredoxin domain containing 5 (TXNDC5) is a recently discovered member of the protein disulfide isomerase family (PDI), which is mainly involved in the proper folding of and the correct formation of disulfide bonds in newly synthesized proteins via its disulfide isomerase and chaperone activities. Although the structural and functional features of mammalian TXNDC5 have been explored in previous studies, no studies have reported the functional characteristics of TXNDC5 in teleost fish. In this study, we report the identification and characterization of TXNDC5 from big-belly seahorse ( Hippocampus abdominalis ) ( ShTXNDC5 ) accompanied by functional studies. The in-silico analysis revealed that the gene encodes a 433 amino acid (aa) long polypeptide chain with a predicted molecular weight of 49.3 kDa. According to homology analysis, ShTXNDC5 shares more than 55% sequence similarity with other teleost TXNDC5 proteins, and the alignment of the gene sequence convincingly reflects the accepted phylogeny of teleost. Analysis of the spatial distribution of ShTXNDC5 expression showed that its highest expression was observed in the ovary, gill, and pouch of seahorses. Moreover, significant upregulation of ShTXNDC5 transcription was noted in seahorse blood and kidney tissues in a time-dependent manner upon viral and bacterial immune challenges. Furthermore, considerable NADPH turnover, insulin reduction ability and significant cell survival effects of ShTXNDC5 were determined by the functional assay, revealing its capability to overcome cellular oxidative stress. Altogether, these findings expand our understanding of TXNDC5 at the molecular and functional levels, and its putative role in seahorse immunity. Highlights: We identified thioredoxin domain containing 5 from big-belly seahorse (ShTXNDC5). ShTXNDC5 revealed with 433 amino acids. ShTXNDC5 was highly expressed in the ovary of un-challenged seahorses. ShTXNDC5 mRNA expression level significantly increased after immune challenge. Significant reduction abilities and cell survival capability of ShTXNDC5 were measured.